Dynamic self-organization of side-propelling colloidal rods: experiments and simulations. Issue 48 (21st November 2016) - Vutukuri, Hanumantha Rao; Preisler, Zdeněk; Besseling, Thijs H.; van Blaaderen, Alfons; Dijkstra, Marjolein; Huck, Wilhelm T. S.
Abstract : Fluorescently labeled side-propelling colloidal rods are used to study how shape anisotropy and propulsion direction affect the dynamic self-organization of internally driven colloids on a single particle level. Abstract : In recent years, there is a growing interest in designing artificial analogues of living systems, fueled not only by potential applications as 'smart micro-machines', but also by the demand for simple models that can be used to study the behavior of their more complex natural counterparts. Here, we present a facile, internally driven, experimental system comprised of fluorescently labeled colloidal silica rods of which the self-propulsion is powered by the decomposition of H2 O2 catalyzed by a length-wise half Pt coating of the particles in order to study how shape anisotropy and swimming direction affect the collective behavior. We investigated the emerging structures and their time evolution for various particle concentrations in (quasi-)two dimensional systems for three aspect ratios of the rods on a single particle level using a combination of experiments and simulations. We found that the dynamic self-organization relied on a competition between self-propulsion and phoretic attractions induced by phoresis of the rods. We observed that the particle clustering behavior depends on the concentration as well as the aspect ratio of the rods. Our findings provide a more detailed understanding of dynamic self-organization of anisotropic particles and the role the propulsion direction plays in internally driven systems.